Workshop Optimalisasi Pembelajaran Matematika melalui Aplikasi Scratch menggunakan Konteks Kuliner Lokal - Lucy Asri Purwasi; Nyimas Aisyah; Yusuf Hartono; Budi Mulyono (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2026)
This activity aims to facilitate the understanding and skills of teachers and prospective teachers in using the Scratch application for mathematics learning based on the local culinary context. This activity involved 76 participants who attended an online workshop on March 10, 2026. The workshop consisted of five stages: coordination and needs analysis, material development, workshop implementation, evaluation and reflection, and data analysis and reporting. The methods used included lectures, practice and demonstrations, discussions, and questions and answers. The instruments used in this activity were test questions and questionnaires. Data analysis was conducted using quantitative and qualitative descriptive approaches. The results of the pretest and posttest analysis showed a significant increase in the average score of participants, from 52 in the pretest to 80.5 in the posttest. The evaluation questionnaire showed that most participants felt the material presented was relevant and useful, despite challenges in using Scratch. The use of the local culinary context proved effective in improving participants' understanding and motivation in teaching mathematics. Overall, this activity successfully improved participants' skills in designing mathematics learning that is more creative, relevant, and in accordance with the needs of 21st-century digital literacy.